An action in the perspective of digital inclusion that enables access to rights in UFSM: experience report - Ezequiel Müller , Adauton; Souza Baroni Silveira , Clarita; Elís Perske, Ketlin (Seven Editora, 2023)
This paper aims to report the experience of the activities of transposition of the process of delivery of documents to the Selection Process of Socioeconomic Benefit (BSE) at the Federal University of Santa Maria, during the period of suspension of administrative and academic activities of the Federal Institutions of Higher Education (IFES), due to the Coronavirus pandemic (SARS-Cov-2). It is the result of participant observation performed by authors who are Technical-Administrative Servants in Education (TAES) with the Student Care Center (NAE) and the Administrative Secretariat of the Pro-Rectory of Student Affairs (PRAE) at the Federal University of Santa Maria. The study is based on the actions of the National Student Assistance Plan (PNAES), which at UFSM are materialized by the Socioeconomic Benefit Program (BSE) and discussions about digital inclusion. The aim of this study is to reflect on the potential of measures in the field of digital inclusion, as an opportunity to access students with social vulnerability to their rights. It is structured as a research of qualitative, exploratory approach and applied to the context of professional performance of researchers. The data were constructed through qualitative, bibliographic and documentary research and participant observation. The study points out that the adoption of the delivery of documents to the BSE selection process by UFSM, organized digitally, through the Socioeconomic Benefit Portal, streamlines the process of delivery of documents and, consequently, socioeconomic evaluation, allowing students in situations of social vulnerability to access the BSE Program, as well as having guaranteed their right to Student Assistance. DOI: https://doi.org/10.56238/tfisdwv1-051